Amarogentin, a Secoiridoid Glycoside, Abrogates Platelet Activation through PLCγ2-PKC and MAPK Pathways. (29th April 2014) - Yen, Ting-Lin; Lu, Wan-Jung; Lien, Li-Ming; Thomas, Philip Aloysius; Lee, Tzu-Yin; Chiu, Hou-Chang; Sheu, Joen-Rong; Lin, Kuan-Hung
Abstract : Amarogentin, an active principle of Gentiana lutea, possess antitumorigenic, antidiabetic, and antioxidative properties. Activation of platelets is associated with intravascular thrombosis and cardiovascular diseases. The present study examined the effects of amarogentin on platelet activation. Amarogentin treatment (15~60  μ M) inhibited platelet aggregation induced by collagen, but not thrombin, arachidonic acid, and U46619. Amarogentin inhibited collagen-induced phosphorylation of phospholipase C (PLC) γ 2, protein kinase C (PKC), and mitogen-activated protein kinases (MAPKs). It also inhibits in vivo thrombus formation in mice. In addition, neither the guanylate cyclase inhibitor ODQ nor the adenylate cyclase inhibitor SQ22536 affected the amarogentin-mediated inhibition of platelet aggregation, which suggests that amarogentin does not regulate the levels of cyclic AMP and cyclic GMP. In conclusion, amarogentin prevents platelet activation through the inhibition of PLC γ 2-PKC cascade and MAPK pathway. Our findings suggest that amarogentin may offer therapeutic potential for preventing or treating thromboembolic disorders.